2015
DOI: 10.1016/j.freeradbiomed.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin rod-derived cone viability factor protects against photooxidative retinal damage

Abstract: Rod-derived cone viability factor (RdCVF) is a trophic factor of the thioredoxins family that promotes the survival of cone photoreceptors. It is encoded by the nucleoredoxin-like gene 1 Nxnl1 which also encodes by alternative splicing a long form of RdCVF (RdCVFL), a thioredoxin enzyme that interacts with TAU. The known role of thioredoxins in the defense mechanism against oxidative damage led us to examine the retinal phenotype of the Nxnl1(-/-) mice exposed to photooxidative stress. Here we found that, in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 43 publications
(58 reference statements)
0
40
0
2
Order By: Relevance
“…RdCVF, a truncated thioredoxin-like protein lacking thioloxidoreductase activity, was identified by high content screening of a mouse retinal cDNA library on cone-enriched cultures from chicken embryos (Lé veillard et al, 2004). RdCVF is an alternative splice variant of the nucleoredoxin-like 1 (Nxnl1) gene, whose other splice product is RdCVFL, an active thioredoxin that protects its binding partner, the microtubule associated protein TAU, from oxidation and aggregation (Elachouri et al, 2015;Fridlich et al, 2009). Nxnl1 À/À mice experience an age-dependent loss of rod and cone function and cone degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…RdCVF, a truncated thioredoxin-like protein lacking thioloxidoreductase activity, was identified by high content screening of a mouse retinal cDNA library on cone-enriched cultures from chicken embryos (Lé veillard et al, 2004). RdCVF is an alternative splice variant of the nucleoredoxin-like 1 (Nxnl1) gene, whose other splice product is RdCVFL, an active thioredoxin that protects its binding partner, the microtubule associated protein TAU, from oxidation and aggregation (Elachouri et al, 2015;Fridlich et al, 2009). Nxnl1 À/À mice experience an age-dependent loss of rod and cone function and cone degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…This encodes for two products via alternative splicing, a truncated thioredoxin-like protein and the full-length protein, capable of enzymatic activity. The molecule provided exogenously, by intravitreal injection, protects photoreceptor cells in RP mutant mice (Cronin et al, 2010;Elachouri et al, 2015). Conversely, mutants missing RdCVF undergo a progressive photoreceptor loss.…”
Section: Rod-derived Cone Viability Factormentioning
confidence: 99%
“…Nevertheless, since they depend on the rod-derived cone viability factor (RdCVF) 116 , they would disappear after demise of parafoveal rods. It has been demonstrated that RdCVF protects 661W cells from photooxidative damage 117 and, most important, that RdCVFdeficient mice are extraordinarily sensitive to light-induced damage 118 .…”
Section: Photoreceptorsmentioning
confidence: 99%